Seed development-related genes contribute to high yield heterosis in integrated utilization of elite autotetraploid and neo-tetraploid rice - Lu, Zijun; Huang, Weicong; Ge, Qi; Liang, Guobin; Sun, Lixia; Wu, Jinwen; Ghouri, Fozia; Shahid, Muhammad Qasim; Liu, Xiangdong (Frontiers in Plant Science, 2024)
Autotetraploid rice holds high resistance to abiotic stress and substantial promise for yield increase, but it could not be commercially used because of low fertility. Thus, our team developed neo-tetraploid rice with high fertility and hybrid vigor when crossed with indica autotetraploid rice. Despite these advances, the molecular mechanisms underlying this heterosis remain poorly understood. An elite indica autotetraploid rice line (HD11) was used to cross with neo-tetraploid rice, and 34 hybrids were obtained to evaluate agronomic traits related to yield. WE-CLSM, RNA-seq, and CRISPR/Cas9 were employed to observe endosperm structure and identify candidate genes from two represent hybrids. These hybrids showed high seed setting and an approximately 55% increase in 1000-grain weight, some of which achieved grain yields comparable to those of the diploid rice variety. The endosperm observations indicated that the starch grains in the hybrids were more compact than those in paternal lines. A total of 119 seed heterosis related genes (SHRGs) with different expressions were identified, which might contribute to high 1000-grain weight heterosis in neo-tetraploid hybrids. Among them, 12 genes had been found to regulate grain weight formation, including OsFl3, ONAC023, OsNAC024, ONAC025, ONAC026, RAG2, FLO4, FLO11, OsISA1, OsNF-YB1, NF-YC12, and OsYUC9. Haplotype analyses of these 12 genes revealed the various effects on grain weight among different haplotypes. The hybrids could polymerize more dominant haplotypes of above grain weight regulators than any homozygous cultivar. Moreover, two SHRGs (OsFl3 and SHRG2) mutants displayed a significant reduction in 1000grain weight and an increase in grain chalkiness, indicating that OsFl3 and SHRG2 positively regulate grain weight. Our research has identified a valuable indica autotetraploid germplasm for generating strong yield heterosis in combination with neo-tetraploid lines and gaining molecular insights into the regulatory processes of heterosis in tetraploid rice.